ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAANMANUFAKTUR YANG TERDAFTAR PADA BEI(BURSA EFEK INDONESIA) - B11108152, WENDA (Jurnal Manajemen Update, 2013)
This research was conducted to examine the effect of Return on Asset (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER) and the Size of the stock return manufacturing companies listed on the Indonesia Stock Exchange, either simultaneously or partially. Object in this study is a manufacturing company listed on the Indonesia Stock Exchange in the period 2007 to 2010. Which amount to 10 companies. Data analysis was conducted using multiple linear regression analysis model. The hypothesis in this study be evidenced using a statistical test. F test for simultaneous testing and t test for partial testing. According to analysis conducted found that the Return On Asset ( ROA ), Earning Per Share ( EPS ), Debt to Equity Ratio (DER) and Size effect simultaneously on stock return manufacturing companies listed on the Indonesia Stock Exchange but partially indicated that Earning Per Share (EPS) and Size that effect stock return, while Return On Asset (ROA) and Debt to Equity Ratio (DER) not effect on stock return manufacturing companies listed on the Indonesia Stock Exchange. Keyword : Return On Asset (ROA), Earning Per Share (EPS) Debt to Equity Ratio (DER), Size and stock return.